Pengaruh Brand Ambassador terhadap Minat Beli Produk Click di Kota Bandung - Kodariyah, Turaudatul; Kusnadi, Hani Kustyanti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to find out how the influence of Brand Ambassadors on Purchase Intentions in the City of Bandung. This research method uses a descriptive quantitative research method. The population of this research is fans of NCT 127, namely nctzen in the city of Bandung. The sample chosen by the researcher was a non-probability sampling of 100 respondents and a questionnaire as a data collection tool with a Likert scale. The analysis technique used is validity test, reliability test, normality test, R2 analysis, and t test. The results of this study state that there is a significant influence from Brand ambassadors on Interest in Buying Click products in the city of Bandung which has a tcount of 14.623 which is greater than the ttable of 1.960. So that in the R2 analysis, the influence of the independent variable (X) brand ambassador on the dependent variable (Y) purchase intention is 68.8%, while there are other factors not examined by the authors in this study that affect 31.4%.